Genetic Regulation of Development in Sorghum bicolor (VIII. Shoot Growth, Tillering, Flowering, Gibberellin Biosynthesis, and Phytochrome Levels Are Differentially Affected by Dosage of the ma3R Allele. - Foster, K. R. (1994)
Sorghum [Sorghum bicolor (L.) Moench] homozygous for ma3R lacks a type II, light-stable phytochrome of 123 kD and has a number of phenotypic characteristics consistent with the absence of functional phytochrome B. We have used plants heterozygous at Ma3 (Ma3/ma3R and ma3/ma3R) to determine the effect of dosage of ma3R on plant growth, flowering, gibberellin (GA) levels, and content of the 123-kD phytochrome. Both Ma3/ma3R and ma3/ma3R produced the same number of tillers per plant as their respective homozygous non-ma3R parents. Height of the heterozygotes was intermediate between the homozygous parents, although it was more similar to the non-ma3R genotypes. In both field and growth-chamber environments, the timing of floral initiation and anthesis in the heterozygotes also was intermediate, again more similar to non-ma3R plants. In Ma3/ma3R, levels of GA53, GA19, GA20, and GA1 were almost exactly intermediate between levels detected in Ma3/Ma3 and ma3R/ma3R plants. Immunoblot analysis indicated that there was less of the 123-kD phytochrome in Ma3/ma3R than in homozygous Ma3, whereas none was detected in ma3R/ma3R. The degree of dominance of Ma3 and ma3 over ma3R varies with phenotypic trait, indicating that mechanisms of activity of the 123-kD phytochrome vary among the biochemical processes involved in each phenotypic character. Although the heterozygotes were similar to homozygous Ma3 and ma3 plants in growth and flowering behavior, Ma3/ma3R contained 50% less of the bioactive GA (GA1) than non-ma3R genotypes. Thus, sensitivity to endogenous GAs also may be regulated by the 123-kD phytochrome. To fully regulate plant growth and development, two copies of Ma3 or ma3 are required to produce sufficient quantities of the light-stable, 123-kD phytochrome.